Excess cash reserves and acquisition behaviour: Evidence from European acquisitions - Kaunisto, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2017)
This study examines the informational aspects of corporate cash reserves and tests whether there is a relation between excess cash reserves and acquisition behaviour. The two core theories presented in this study, the agency theory and the precautionary motive, are based on the contrasting premises of principle-agent relations and these differences have been examined to achieve the stated main objective. The agency theory predicts that some managers pursue their own objectives, such as empire building, at the expense of current shareholders. Consequently, these managers make more and worse acquisitions, when there are excess cash reserves available. On the contrary, the precautionary motive assumes that financially constrained firms are reluctant to deploy their cash reserves and consequently are less likely to make acquisitions. This study reports results based on three data sets that have been used to first determine optimal cash reserve ratios and then to examine acquisition behaviour. The data has been retrieved from Thomson Reuters Datastream and SDC Platinum and it contains all public companies domiciled in the EU-15 countries and information on the acquisitions made by these companies in the period 2005–2015. OLS and probit regressions have been used to test the impact of excess cash reserves on acquisition likelihood, chosen payment type and acquirer announcement effects. The results presented in this study show that neither the agency theory nor the precautionary motive is fully able to explain acquirer cash reserve effects in all observed stages of acquisitions. Cash-rich firms are less active acquirers compared to other firms which strongly contradicts the predictions of the agency theory but is consistent with the precautionary motive. In general, the choice of the method of payment does not appear to be affected by the amount of excess cash reserves. However, as the precautionary motive predicts, cash-rich firms finance a greater proportion of their acquisitions with stock when the level of information asymmetry is low. Investors seem to interpret the increased activity as a negative sign, since the cash-rich firms have the lowest abnormal announcement returns when the amount of asymmetric information is low. Overall, the findings suggest that the precautionary motive is more relevant of these two theories in understanding the informational aspects of corporate cash holdings.